Broadband Equivalent Circuit Model for a Coplanar Waveguide Line Loaded with Split Ring Resonators - Victor Sanz; Angel Belenguer; Alejandro L. Borja; Joaquin Cascon; Hector Esteban; Vicente E. Boria (International Journal of Antennas and Propagation)
A new equivalent circuit for a coplanar waveguide loaded with split ring resonators is presented. The traditional circuits that model these devices are only able to characterize the left-handed propagation band, and their response is very similar to the real one within a very limited bandwidth. In contrast, this proposed broadband equivalent circuit is able to portray not only the left-handed propagation band, but also the right-handed one that occurs at higher frequencies. Besides, the response of this kind of basic cells can be adjusted with the proposed circuit model in a bandwidth close to a decade.